Energy consumption: Characteristics and user’s attitude / Azman Arifin - Arifin, Azman (2003)
The effects of the wall openings, infiltration and human occupancy to the air conditioning characteristics, such as temperature and relative humidity are analyzed and the information is then used to estimate the annual energy consumption. Actually, the heat energy is produced to the surrounding by human or people that occupy the building. The current temperature and the relative humidity will be affected when somebody stays in the air-conditioned room. The effects to the air conditioning characteristics depending on the number of occupancy is studied. As for the infiltration and wall openings effects, the energy usage and how the problems of the effects should be eliminated are focused. Hence, the effects of air conditioning characteristics due to the three factors stated above can be observed and the energy use and how the energy in building can be saved are discovered.